2019
DOI: 10.1587/elex.16.20190461
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance MPPT algorithm combining advanced three-point weight comparison and temporary stopped running strategy for PV systems

Abstract: This paper proposes a new maximum power point tracking (MPPT) control strategy, including a boost converter temporary stopped running (TSR) strategy and an advanced three-point weight comparison method (ATPWC). The proposed ATPWC was used to detect three power points of a photovoltaic (PV) module output, and a microcontroller unit (MCU) was used to calculate the slope of the three power points and to perform MPPT so as to improve the system's conversion efficiency. The proposed method was successfully applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, this algorithm has the following shortcomings: (1) under the partial shading condition (PSC), the actuating point can become stuck at the local peak power point without escape [37]; (2) at a steady-state irradiance level, the actuating point will vibrate near the MPP [21]; (3) with the rapid change in irradiance levels, the actuating point cannot capture the MPP in time [22]; (4) the actuating point is close to the MPP, and the convergence speed is slow [22].…”
Section: Perturbation and Observation Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this algorithm has the following shortcomings: (1) under the partial shading condition (PSC), the actuating point can become stuck at the local peak power point without escape [37]; (2) at a steady-state irradiance level, the actuating point will vibrate near the MPP [21]; (3) with the rapid change in irradiance levels, the actuating point cannot capture the MPP in time [22]; (4) the actuating point is close to the MPP, and the convergence speed is slow [22].…”
Section: Perturbation and Observation Algorithmmentioning
confidence: 99%
“…Liu et al reorganized the three power point technique, then searched for the MPP [21]. Liu et al discussed a provisional stopped operating strategy and the three power point method for a PV system [22]. Saito et al developed the eliminated MPPT oscillation method for solar power systems and confirmed it was feasible by the dynamic I-V curve [23].…”
Section: Introductionmentioning
confidence: 99%
“…It involves disrupting the duty cycle of a power converter to affect P pv for MPPT. (18) However, the disruptive character of the algorithm causes the actuating point to oscillate around the MPP, resulting in suboptimal power output. In addition, the algorithm compares the power points only with the adjacent power points.…”
Section: Hc Algorithmmentioning
confidence: 99%
“…An enhanced PSO method was put forth by Premkumar et al [10] with the goal of capturing the global maximum power point (GMPP) faster, more precisely, and with less chattering of the power curve. Liu and Lu are [11]. A high-performance MPPT algorithm that combines a temporary running strategy and a sophisticated three-point weight comparison.…”
Section: Introductionmentioning
confidence: 99%